Healing from Healer: Use of Traditional Health Services in the Age of Modern Health - Syaiful, Muhammad; Hakim, Arif Rahman; Hak, Imamul (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
The phenomenon of traditional health practices is still being used by some people, the unique thing is that those who take advantage of this health service do not only come from underprivileged segments of society but are also often used by the rich. Moreover, this phenomenon occurs during the existence of a modern health industry whose access is increasingly accessible to all people. Traditional medicine or so-called alternative medicine that uses plant-based medicines (herbal) or other media. Not only in the area of medicine, but this research also describes traditional healers or as local, sanro, as an alternative to modern health industry practices. This study uses an ethnographic method with a participatory-observative approach to understanding in-depth the practice of alternative medicine. Field research focus in the district. Somba Opu, Gowa Regency, South Sulawesi. Where the distribution of modern health facilities in the capital of this sub-district is higher than in other sub-districts. The results of the study indicated that the medical instruments performed by traditional healers, apart from using traditional herbs in the form of special plants, also used mantras written in the book using Arabic letters. Some of the traditional medicinal methods in maintaining their existence are carried out, both in the form of good health services, trying to prove the efficacy of the treatment, and strengthening their networks with doctors and fellow sanro outside the District of Gowa.